Lineament Domain of Regional Strike-Slip Corridor: Insight from the Neogene Transtensional De Geer Transform Fault in NW Spitsbergen - CIANFARRA, Paola; SALVINI, Francesco (Pure and Applied Geophysics, 2014)
Lineaments on regional scale images represent controversial features in tectonic studies. Published models explain the presence of the lineament domains in most geodynamic environments as resulting from the enhanced erosion along strikes normal to the upper crustal regional extension. Despite their success in many tectonic frameworks, these models fail to explain the existing lineament domains in the regional strike-slip corridors that separate regional blocks, including the transform faults. The present paper investigates the lineament distribution in such environments, and specifically presents the results from a study along the shear corridor of the De Geer Transform Fault in the North Atlantic, responsible for the separation and drifting away between Northern Greenland and the Svalbard Archipelago since Oligocene times. The study spans from satellite image analysis and outcrop scale investigations to a more regional analysis on a digital bathymetric model of the North Atlantic–Arctic Ocean. Lineaments were automatically detected in the spectral band 8 (0.52–0.9 lm) of a Landsat 7 image (15 m/pixel resolution). A total of 320 image lineaments were extracted from both the regional and the local scale investigations and statistically analyzed. Results from the multi-scalar lineament analyses revealed the existence of a main N–S lineament domain regionally persistent from the De Geer corridor to the western margin of northern Spitsbergen where it relates to the youngest, post-Oligocene, tectonics observed onshore. This is confirmed by field observations showing that the N–S faults represent the youngest brittle deformation system and systematically cut the deformations associated with the building of the Tertiary West Spitsbergen fold and thrust belt. The N–S lineament domain is the result of the activity of a larger, regional scale tectonic feature, NW–SE oriented and responsible for the localized extension within its deformation corridor, the De Geer Transform Fault. A model is presented that involves the ...